2011
DOI: 10.1111/j.1349-7006.2011.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral efficacy by systemic delivery of heparin conjugated polyethylenimine–plasmid interleukin‐15 complexes in murine models of lung metastasis

Abstract: Gene therapy shows promising application in cancer therapy, but the lack of an ideal gene delivery system is still a tough challenge for cancer gene therapy. Previously, we prepared a novel cationic nanogel, heparin-polyethylenimine (HPEI), which had potential application in gene delivery. In the present study, we constructed a plasmid with high expression efficiency of interleukin-15 (IL15) and investigated the effects HPEI-plasmid IL15 (HPEI-pIL15) complexes on the distribution level of the lung. We then eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The results have shown HPEI nanoparticles to be a novel nonviral gene carrier with promising application in cancer gene therapy. 29,48 In this work, we prepared a plasmid-expressing ms-T34A gene and used HPEI nanoparticles to deliver this gene to treat colon cancer in vitro and in vivo. The anticancer effect of HPEI nanoparticle-mediated ms-T34A gene therapy was evaluated, and the relevant anticancer mechanisms are discussed.…”
Section: Resultsmentioning
confidence: 99%
“…The results have shown HPEI nanoparticles to be a novel nonviral gene carrier with promising application in cancer gene therapy. 29,48 In this work, we prepared a plasmid-expressing ms-T34A gene and used HPEI nanoparticles to deliver this gene to treat colon cancer in vitro and in vivo. The anticancer effect of HPEI nanoparticle-mediated ms-T34A gene therapy was evaluated, and the relevant anticancer mechanisms are discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Anionic polymer or its conjugate Cationic polymer or liposome Reference pDNA ᵞPGA Chitosan [66,67] pDNA ᵞPGA Dendrigraft poly-L-lysine [80] pDNA ᵞPGA PEI [81][82][83] pDNA ᵞPGA Protamine [75] pDNA αPGA DOTAP/Chol liposome [54] siRNA ᵞPGA Chitosan [73] siRNA ᵞPGA Dendrigraft poly-L-lysine [74] siRNA αPGA DOTAP/Chol liposome [77] siRNA αPGA DMAPAP/DOPE liposome [78,79] siRNA ᵞPGA PEI [76] pDNA Heparin Cationic glycopolymer (Tr4) [84] pDNA Heparin-PEI - [85] pDNA Alginic acid, Pectin Lipofectamine 2000 [24] pDNA: plasmid DNA, siRNA: small interfering RNA, ᵞPGA: poly-ᵞ-glutamic acid, αPGA: poly-α-glutamic acid, PEI: polyethylenimine, DMAPAP: 2-{3-[bis-(3-amino-propyl)-amino]-propylamino}-N-ditetradecyl carbamoyl methylacetamide, Chol: cholesterol, DOPE: 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine.…”
Section: Nucleic Acidmentioning
confidence: 99%
“…They speculated that heparin coating of the polyplexes appeared to improve cell surface binding, internalization, intracellular traf icking of polyplexes to the nucleus, leading to high transgene expression. Furthermore, chemically conjugated PEI with heparin (heparin-PEI) formed a nanogel, and intravenous injection of heparin-PEI and pDNA complexes ( Figure 5B) exhibited high distribution of pDNA in the lung, and inhibited lung metastasis of malignant melanoma B16-F10 and mouse colon carcinoma Colon 26 by injection of pDNA encoding interleukin 15 gene [85], indicated that the heparin-PEI conjugate is an ef icient gene carrier to the lung.…”
Section: Nucleic Acidmentioning
confidence: 99%
“…They used heparin-conjugated PEI for the delivery of therapeutic gene pIL15 (encoding interleukin-15) in murine models of lung metastasis. The post-treatment therapeutic assessment indicated apoptosis and inhibition of cell proliferation in lung tumor foci, which could curb the growth of cancer cell mass to a great extent [57].…”
Section: Poly(ethyleneimine)mentioning
confidence: 99%